Studi eksperimental variasi media pendingin dan holding time tempering terhadap kekerasan material pengganti pin track link excavator 305.5E2 - Auliana Diah Wilujeng; Misbakhul Fatah; Laily Ulfiyah (Universitas Muhammadiyah Metro, 2023)
The frequency of using heavy equipment that exceeds capacity often occurs in construction projects. This can cause components to fail or wear out as in track link pin components. Therefore, this study aims to obtain a good quality of heat treatment using quenching and tempering methods, to the hardness values of AISI 1045 and AISI 1037 steels for replace the track link pin components of Excavator 305.5E2. In this study, the method of heat treatment is hardening with a temperature of 800â„ƒ. After that it is cooled quickly using water and oil media. After that, the specimens were tempered based on differences in holding times of 30, 35, 40 minutes. Specimens that have been heat treated will be tested using a hardness test using the Vickers method. From the results of this study, it was found that the effect of the cooling medium and holding time on the hardness value of AISI 1045 steel. At a holding time of 30 minutes the hardness value was 41.5 HRC. Meanwhile, in water media at a holding time of 30 minutes, the hardness value is 32.2 HRC.